Glycosyl-Nucleolipids as New Bioinspired Amphiphiles - Philippe Barthélémy; Eric Amigues; Amit Patwa; Laurent Latxague (Molecules, 2013)
Four new Glycosyl-NucleoLipid (GNL) analogs featuring either a single fluorocarbon or double hydrocarbon chains were synthesized in good yields from azido thymidine as starting material. Physicochemical studies (surface tension measurements, differential scanning calorimetry) indicate that hydroxybutanamide-based GNLs feature endothermic phase transition temperatures like the previously reported double chain glycerol-based GNLs. The second generation of GNFs featuring a free nucleobase reported here presents a better surface activity (lower glim) compared to the first generation of GNFs.